2020
DOI: 10.1007/s11366-020-09702-7
|View full text |Cite
|
Sign up to set email alerts
|

The Sincerest Form of Flattery: Nationalist Emulation during the COVID-19 Pandemic

Abstract: As COVID-19 rapidly spread across the globe, every government in the world has been forced to enact policies to slow the spread of the virus. While leaders often claim responses are based on the best available advice from scientists and public health experts, recent policy diffusion research suggests that countries are emulating the COVID-19 policies of their neighbors instead of responding to domestic conditions. Political and geographic considerations play a role in determining which countries imitate one an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
1
15
0
2
Order By: Relevance
“…The rise of nationalism on a global scale during COVID-19 has become a big concern [ 8 , 20 , 21 , 28 34 ]. While the nationalist sentiment reflected in the debate about the Wuhan Diary has been most intense in China, it sent ripples through Chinese communities worldwide.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The rise of nationalism on a global scale during COVID-19 has become a big concern [ 8 , 20 , 21 , 28 34 ]. While the nationalist sentiment reflected in the debate about the Wuhan Diary has been most intense in China, it sent ripples through Chinese communities worldwide.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has exacerbated a wave of nationalism that has been growing in intensity over the last decade, reinforcing preexisting nationalist and protectionist waves [1,30]. Exclusionary nationalism during the COVID-19 pandemic has increased the decoupling of international exchanges, adversely affecting the strategic environment in which Australia acts as a middle power.…”
Section: Covid-19 the Rise Of Nationalism And Australia's Ontological Insecuritymentioning
confidence: 99%
“…Recent research on policy‐making during the Covid‐19 pandemic has found evidence that governments have been influenced by the policy choices of other governments and have drawn lessons from each other. Yet these studies focus either on a single case study such as Cyprus (Petridou et al 2020), on nationalist regimes in different world regions that have emulated each other (Givens and Mistur 2021), or on factors such as government capacity, societal trust, or party preferences that may have caused variety among national responses (Toshkov et al 2020), rather than on the patterns and mechanisms of policy diffusion.…”
Section: Policy Diffusion In Times Of the Covid‐19 Pandemicmentioning
confidence: 99%